Implementasi Desain Kurikulum Muadalah di Pondok Pesantren Darussalam Ciomas Bogor - Fachru Abdul Rahman; Qowaid Qowaid; Efrita Norman (Jurnal Dirosah Islamiyah, 2023)
This muadalah curriculum is an independent curriculum according to the boarding school that developed it, curriculum independence includes aspects in determining teaching materials, assessment systems, and learning processes. This study uses a qualitative approach. The data collection was carried out by sourced from several documents of the muadalah curriculum contained in the boarding school, as well as interviews with parties related to the muadalah curriculum, and observations of researchers with field reviews of the process of implementing the learning of the muadalah curriculum at Islamic boarding schools. Darussalam. The results of the research show that the type of curriculum design is the Darussalam Islamic Boarding School, including the type of separated subject curriculum design. The subject curriculum consists of separate subjects, and "the subject is a collection of experience and knowledge organized logically and mathematically" by curriculum experts. Knowledge-centered curriculum design is designed based on the discipline structure, therefore this design model is also called the academic subject curriculum model. There are two factors that influence the implementation of the curriculum of the muadalah Islamic boarding school in Darussalam Islamic Boarding School, namely the supporting factors and the inhibiting factors. Supporting factors in the implementation of the curriculum, namely, the provision of qudwah hasanah from all boarding school stakeholders, the formation of a good environment, the competence of teachers according to their fields, teacher discipline in preparing materials, the relationship between students and supervisors, facilities and infrastructure, the boarding school environment. And the inhibiting factors are that there are still some teachers who lack mastery of the material, programs that have not been achieved, inadequate facilities, human resources in recording emissions that are not yet qualified. The solution to overcome the inhibiting factors in the "implementation of the Darussalam Islamic Boarding School curriculum, namely by determining the supervisor of the senior teacher "to provide guidance and direction, ta'hil is carried out to all teachers." Keywords: Design, Curriculum Implementation, Muadalah, Islamic Boarding School‎